2012
DOI: 10.1007/s00339-012-6858-x
|View full text |Cite
|
Sign up to set email alerts
|

Surface plasmon optical sensor with enhanced sensitivity using top ZnO thin film

Abstract: Surface plasmon resonance (SPR) is one of the most sensitive label-free detection methods and has been used in a wide range of chemical and biochemical sensing. Upon using a 200 nm top layer of dielectric film with a high value of the real part ε of the dielectric function, on top of an SPR sensor in the Kretschmann configuration, the sensitivity is improved. The refractive index effect of dielectric film on sensitivity is usually ignored. Dielectric films with different refractive indices were prepared by rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…With the inclusion of GO, the SPR sensitivity for the Ag/CS-GO was enhanced to 1.38° ppm −1 compared to the sensitivity of the Ag/CS thin film. Reports point out that a sharper resonance curve means that a better resolution may enhance the surface plasmon resonance, and thus it increases the sensitivity [17]. This statement agreed well with the sharper resonance curve in Figure 8b compared to Figure 8a.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…With the inclusion of GO, the SPR sensitivity for the Ag/CS-GO was enhanced to 1.38° ppm −1 compared to the sensitivity of the Ag/CS thin film. Reports point out that a sharper resonance curve means that a better resolution may enhance the surface plasmon resonance, and thus it increases the sensitivity [17]. This statement agreed well with the sharper resonance curve in Figure 8b compared to Figure 8a.…”
Section: Resultssupporting
confidence: 83%
“…The SPR is an optical process in which p-polarized light causes the excitation of a charge density wave along the metal–dielectric material interface by satisfying a resonance condition [16]. In other words, at a certain incident angle, when the wave vector of incident light matches the wave vector of the surface plasmon wave, a sharp dip is produced in the reflectivity curve [17]. A thin metallic layer such as a gold (Au) or silver (Ag) layer is usually used to excite the surface plasmon wave on the SPR surface.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Lahav et al [ 13 ] facilitated sensitivity enhancement by using a guided-wave SPR structure, which was prepared by evaporating a 10 nm Si layer on top of the metal. Shukla et al [ 14 ] and Bao et al [ 15 ] both demonstrated that the sensitivity of an SPR sensor could be increased by adding a ZnO thin film. Besides, Benkabou et al [ 16 ] achieved sensitivity enhancement by employing the dielectric multilayer structure in the SPR sensor.…”
Section: Introductionmentioning
confidence: 99%
“…Nearly four times angular sensitivity has been achieved by adding a 10 nm Si film on top of a conventional SPR sensor. Besides, Shukla et al [16] and Bao et al [17] demonstrated a top ZnO layer is effective in enhancing the sensitivity of a fiber-type and prismtype SPR sensor respectively. Benkabou et al [18] achieved the sensitivity enhancement by employing a dielectric multilayer structure in a SPR sensor.…”
Section: Introductionmentioning
confidence: 99%